Dripping and vape tricks: Alternative e-cigarette use behaviors among adolescents. (August 2020) - Kong, Grace; Morean, Meghan E.; Bold, Krysten W.; Wu, Ran; Bhatti, Harmanpreet; Simon, Patricia; Krishnan-Sarin, Suchitra
Highlights: 21% of ever e-cigarette users ever dripped and 55% ever conducted vape tricks. The most frequently endorsed flavors used for both behaviors were fruit, candy, and mint. Nicotine concentrations for dripping was 3 mg and for vape tricks was 0 mg. Source for learning these behaviors were friends. Risky tobacco use behaviors were associated with dripping and vape tricks. Abstract: Introduction: E-cigarettes appeal to adolescents because of alternative uses, such as dripping (i.e., applying e-liquid directly on the atomizer) and conducting vape tricks (i.e., creating shapes from exhaled aerosol). However, little is known about these behaviors and adolescents who engage in these behaviors. Methods: Using cross-sectional surveys from 4 high schools in Connecticut in 2017 (N = 2945), we assessed the frequency of dripping and conducting vape tricks, product characteristics (e.g., nicotine, flavor) used for these behaviors, and where adolescents learn about these behaviors. We also conducted multinomial logistic regression analysis to assess whether demographics, age of e-cigarette use onset, past-month-use of e-cigarettes, and lifetime use of other tobacco products were associated with dripping and/or vape tricks. Results: Among ever e-cigarette users (N = 1047), 20.5% ever dripped and 54.9% ever conducted vape tricks. The most frequently endorsed 1) flavors used for both behaviors were fruit, candy, and mint, 2) nicotine concentrations used for dripping was 3 mg and for vape tricks was 0 mg, and 3) the top source for learning these behaviors were friends. The multinomial model showed that earlier age of e-cigarette use onset, past-month-use of e-cigarettes, and lifetime use of other tobacco products were associated with dripping and vape tricks. Discussion: Engaging in dripping and vape tricks was associated with risky tobacco use behaviors (e.g., earlier age of onset, other tobacco use), and involved exposure to nicotine and flavors. Reducing appeal of dripping and vape tricks and preventing product characteristics that facilitate these behaviors may reduce harm to adolescents.